Sistem Pakar Deteksi Penyimpangan Perkembangan dan Perilaku Emosional Anak Berdasarkan KPSP dan KMPE Berbasis Android - Dinda Rahmah Ifani; Shumaya Resty Ramadhani (Politeknik Negeri Bengkalis, 2023)
Parents are one of the most important factors concerned with the development of a child. Parents need to pay attention to how a child grows physically and psychologically. Conducting early examinations on children is an important thing for parents to see problems with developmental deviations and children's emotional behavior. Most parents do not have time and have problems checking their children at health services. One solution that can be done is to build an application for early detection of developmental deviations and children's emotional behavior based on Android-based KPSP and KMPE. This system was built using the forward chaining method based on an expert knowledge base and using the Firebase database. This system was tested by testing User Acceptance Testing and also the System Usability Scale, based on the UAT results the system and its functions are as expected. And based on the results of the SUS test, a value of 97.5% was obtained, which means that this system is acceptable to the community. This system has also been validated by experts. With this application, the results obtained are the realization of an Android-based expert system for developmental deviations and child emotional behavior that can make it easier for parents to efficiently detect potential deviations in child emotional development and behavior.